Simulation study on the vehicle speed control in longitudinal direction using a new Continuously Variable Transmission (CVT) System / Muhammad Luqman Hakim Abd Rahman ... [et al.] - Abd Rahman, Muhammad Luqman Hakim; Hudha, Khisbullah; Abd Kadir, Zulkiffli; Amer, Noor Hafizah; Murrad, Muhamad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
In order to study the capability of Continuously Variable Transmission (CVT) system, a model of High Mobility Multipurpose Wheeled Vehicle (HMMWV) is derived and carried out in the Matlab-Simulink environment. The model consists of vehicle dynamic system, wheel dynamic system, powertrain system and tire traction system where the performance of vehicle model is compared between a stepped Automatic Transmission (AT) and CVT system equipped to the vehicle. The model is verified using CarSim results where the developed model shows a similar trend with minor deviation. A new electro-mechanical CVT system has been proposed to overcome the drawbacks of the current CVT system. Then, the developed vehicle model is implemented with vehicle speed control to study the performance of the vehicle with both transmission systems. Comparison between AT and CVT systems indicate that vehicle with CVT system shows a superior performance with higher acceleration performance and lower fuel consumption.